Application Terrasar-X data for studying land subsidence in Hanoi City - Anh, Nguyen Duc; Cuong, Tran Quoc; Anh, Tran Van; The, Hoang Anh; Thanh, Nguyen Trung; Thang, Nguyen Huy (Vietnam Journal of Earth Sciences, 2019)
SAR Interferometry (InSAR) is a technique to measure land subsidence and can build a subsidence map on a large spatial scale with high accuracy. The study presented the application of PSInSAR for determining the subsidence of the central area of Hanoi through Terrasar-X data set from 2010 to 2015, with 23 images. The result shows that some area has the high subsidence in the districts of Hanoi such as Hoang Mai, Ha Dong and the slow subsidence such as Dong Da, Hai Ba Trung with subsidence velocity is less than -10mm/year. Besides, the correlation between ground subsidence measured by PSInSAR and subsidence monitoring of building CC02 Van Quan in Ha Dong district for the same period was computed with a correlation coefficient (R2) of 0.94. The PSInSAR technique can detect and estimate subsidence phenomena effectively with X-band.1.